Electrode wear and material removal rate during EDM of aluminum and mild steel using copper and brass electrodes - Khan, Ahsan Ali (Springer London, 2008)
In the present study an analysis has been done to evaluate the electrode wear along the cross-section of an electrode compared to the same along its length during EDM of aluminum and mild steel using copper and brass electrodes. In an overall performance comparison of copper and brass electrodes, we found that electrode wear increases with an increase in both current and voltage, but wear along the cross-section of the electrode is more compared to the same along its length. This is due to easier heat transfer along the length compared to the same along the crosssection of the electrode. It was also found that the wear ratio increases with an increase in current. That means, though a higher current causes more removal of work material and the electrode, comparatively more material is removed from the electrode. The highest wear ratio was found during machining of steel using a brass electrode. The low thermal conductivity of brass electrodes causes less heat loss, and its low melting point results in fast melting of the electrode material. At the same time, low thermal conductivity of steel results in poor heat absorption, and its high melting temperature causes poor removal of work material. These factors result in the highest wear ratio during machining of steel using a brass electrode. The highest material removal rate was observed during machining of aluminum using brass electrodes. Comparatively low thermal conductivity of brass as an electrode material does not allow the absorption of much heat energy, and most of the heat is utilized in the removal of material from aluminum workpiece at a low melting point. But during machining of steel using copper electrodes, a comparatively smaller quantity of heat is absorbed by the work material due to its low thermal conductivity. As a result material removal rate becomes very low.